Diversity, inclusion, and bank performance: Evidence from ASEAN 5 and Vietnam - Fadli Septianto; Irwan Trinugroho; Putra Pamungkas (Postgraduate Program Merdeka University, 2026)
This study aims to examine how diversity and inclusion (D&I) affect bank performance in the ASEAN-5 countries and Vietnam. It uses an unbalanced panel dataset of 50 banks across six ASEAN countries from 2012 to 2023. Diversity and inclusion serve as the main independent variable, while return on assets (ROA) and return on equity (ROE) are used as dependent variables. The data are analyzed using a fixed-effects model, with robustness checks conducted using the generalized method of moments (GMM). The findings indicate that inclusion initiatives, as reflected in the inclusion score, are negatively associated with both ROA and ROE. Similarly, the composite measure of diversity and inclusion also shows a negative relationship with bank performance. This study makes three main contributions. First, it provides sector-specific empirical evidence on the relationship between diversity, inclusion, and performance in the banking industry, an area that has received limited attention in prior research. Second, it distinguishes between the effects of diversity and inclusion as separate dimensions. Third, it offers context-specific insights from ASEAN, highlighting how cultural and institutional factors may influence the effectiveness of diversity and inclusion practices.